Evaluation of Transient Motion During Gadoxetic Acid–Enhanced Multiphasic Liver Magnetic Resonance Imaging Using Free-Breathing Golden-Angle Radial Sparse Parallel Magnetic Resonance Imaging. Issue 1 (January 2018) - Yoon, Jeong Hee; Lee, Jeong Min; Yu, Mi Hye; Hur, Bo Yun; Grimm, Robert; Block, Kai Tobias; Chandarana, Hersh; Kiefer, Berthold; Son, Yohan
Abstract : Objectives: The aims of this study were to observe the pattern of transient motion after gadoxetic acid administration including incidence, onset, and duration, and to evaluate the clinical feasibility of free-breathing gadoxetic acid–enhanced liver magnetic resonance imaging using golden-angle radial sparse parallel (GRASP) imaging with respiratory gating. Materials and Methods: In this institutional review board–approved prospective study, 59 patients who provided informed consents were analyzed. Free-breathing dynamic T1-weighted images (T1WIs) were obtained using GRASP at 3 T after a standard dose of gadoxetic acid (0.025 mmol/kg) administration at a rate of 1 mL/s, and development of transient motion was monitored, which is defined as a distinctive respiratory frequency alteration of the self-gating MR signals. Early arterial, late arterial, and portal venous phases retrospectively reconstructed with and without respiratory gating and with different temporal resolutions (nongated 13.3-second, gated 13.3-second, gated 6-second T1WI) were evaluated for image quality and motion artifacts. Diagnostic performance in detecting focal liver lesions was compared among the 3 data sets. Results: Transient motion (mean duration, 21.5 ± 13.0 seconds) was observed in 40.0% (23/59) of patients, 73.9% (17/23) of which developed within 15 seconds after gadoxetic acid administration. On late arterial phase, motion artifacts were significantly reduced on gated 13.3-second and 6-second T1WI (3.64 ± 0.34, 3.61 ± 0.36, respectively), compared with nongated 13.3-second T1WI (3.12 ± 0.51, P < 0.0001). Overall, image quality was the highest on gated 13.3-second T1WI (3.76 ± 0.39) followed by gated 6-second and nongated 13.3-second T1WI (3.39 ± 0.55, 2.57 ± 0.57, P < 0.0001). Only gated 6-second T1WI showed significantly higher detection performance than nongated 13.3-second T1WI (figure of merit, 0.69 [0.63–0.76]) vs 0.60 [0.56–0.65], P = 0.004). Conclusions: Transient motion developed in 40% (23/59) of patients shortly after gadoxetic acid administration, and gated free-breathing T1WI using GRASP was able to consistently provide acceptable arterial phase imaging in patients who exhibited transient motion. Abstract : Supplemental digital content is available in the text.